Evaluation of a prospective radiation oncology departmental team review process using standardized simulation directives. (May 2022) - Kutuk, Tugce; LeGrand, Lorrie A.; Valladares, Maria A.; Rubens, Muni; Chisem, Monique; Quintana, Gabriella; Appel, Haley; Chuong, Michael D.; Hall, Matthew D.; Contreras, Jessika A.; Fagundes, Marcio; Gutierrez, Alonso N.; et al.
Highlights: Change was identified in 20% of simulations using a pre-simulation review process. Standardized pre-simulation review results in an extremely low rate of re-simulation. Simulation modifications increased significant during introduction of telemedicine. Abstract: Introduction: The primary objective of this study is to evaluate the utility and value of an institutional, multi-disciplinary radiation oncology team review process prior to radiotherapy (RT) simulation. Methods: Over a period of 3 months and through an iterative team-based process, a standardized simulation requisition directive (SSRD) was developed, piloted, modified, and subsequently implemented for all patients treated with external beam RT at a single tertiary care institution from January to December 2020. The SSRDs were reviewed at a daily multi-disciplinary radiation oncology team review conference; modifications consequential to the review were prospectively recorded in a quality database. Results: 1500 consecutive SSRDs were prospectively reviewed for this study. 397 modifications on 290 (19.3%) SSRDs were recorded and parsed into 5 main categories and 18 subcategories. The most common modifications resulted from changes in immobilization device ( n  = 88, 22.2%), RT care path ( n  = 56, 14.1%), and arm positioning ( n  = 43, 10.8%). On univariate analysis, modifications were associated with RT intent, scan parameters, tumor site, and consultation type. An increased rate modifications was observed for patients had telemedicine consults ( n  = 101, 22.7%) compared to in-person consultations ( n  = 189, 17.9%) ( p  = 0.032). Using logistic regression analysis, there was also a statistically significant relationship between postoperative RT delivery and modification rates (OR: 2.913, 95% CI: 1.014–8.372) ( p  = 0.0126). Overall, only 14 patients (0.9%) needed re-simulation during the entire study period. Conclusions: Prospective multi-disciplinary radiation oncology team review prior to simulation identifies actionable change in approximately 19% of procedures, and results in an extremely low rate (<1%) of re-simulation. As departmental processes transition to virtual platforms, thorough attention is needed to identify patients at higher risk of simulation modifications.